BUDIDAYA PADI ( Oryza sativa L. ) VARIETAS IPB 9G DENGAN TEKNOLOGI BAPOKOK - Ramadhan, Syahrul; Dulbari, Dulbari; Subarjo, Subarjo; Rahmadi, Rizky (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2025)
IPB 9G Rice Variety is one of the superior varieties newly developed by the Bogor Agricultural Institute, has high yield potential and efficiency in fertilizer and water use. The study aims to determine the growth and yield response of IPB 9G Variety cultivated using the Bapokok planting method. Bapokok technology is a rice cultivation method that emphasizes efficiency in utilizing planting time intervals and production input costs by utilizing straw as a source of organic material that is more environmentally friendly and sustainable. The study was arranged using a Randomized Completely Block Design (RCBD) with six treatments and four replications. The results showed that plant growth did not differ in the treatments tested, producing an average plant height of 135-145 cm, the number of tillers 4-6 stems per clump, with a leaf greenness level of 34-36 (SPAD). Yield conversion per hectare in various Bapokok planting methods ranged from 6-8 tonha-1. The organic Bapokok planting system treatment (P6) on the IPB 9G variety resulted in the highest average conversion yield of 8 tonha-1.